Pengaruh Suhu Dan Waku Sintering Terhadap Pembuatan Foam Glass Menggunakan Limbah Pecahan Kaca Dan Abu Terbang (Fly Ash) Dari Pabrik Sawit - Luci Octaria; Ahmad Fadli; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Foam glass is a material can be used as a insulation acoustic. The objective of this research is to investigate the effect of sintering temperature and time sintering on the physicalproperties of foam glass preparation from sheet glass and fly ash using dolomite as foaming agents. Slurry was made with mixed fly ash 50wt% and powder glass 50wt% incorporated indolomite 8wt% and strirred for 30 minutes; 300 rpm. Slurry was dried in oven at oven 105˚C for for 12 hours. Green bodies removed from mold and then it was sintered in the range 750, 900 and 950 oC at the furnace for 10,20,30 minutes. The effect of sintering temperature andsintering time on the shrinkage, porosity, density, compressive strength, microstructure and crystalline phases (XRD) were investigated. As the sintering temperature range 750oCthe density, compressive strength, shrinkage increased while the percentage of porosity decreased however as sintering temperature 900-950oC density and compressive strengthdecreased but percentage porosity increased. Furthermore, the sintering time increased the bulk density, compressive strength, shrinkage increased while the percentage of porositydecreased. The shrinkage, percentage of porosity, density, and compressive strength of the produced foam glass for insulation were 9,28-20,36%; 63-66%; 0,85-0,91 g/cm3; 1,53-1,69MPa; respectively. The optimum processing for producing foam glass for insulation was to use sintering temperature 900oC, time sintering 30 minutes.Keywords: foam glass; foaming agent; morphology; sintering